The Role of the Cooperative Script Method in Developing Self-Confidence and Public Speaking Skills Among Madrasah Ibtidaiyyah Student - Anshori, Isa; Majid, M. Rofiqul; Fitria, Sufatul; Haq, Ghazwu Fikril (Jurnal Pendidikan Islam, 2024)
The Cooperative Script Method (CSM) has gained prominence as an instructional approach that enhances key student skills, including self-confidence and public speaking abilities. This study aimed to investigate the impact of CSM on students' self-confidence and public speaking skills. The research was conducted at Madrasah Ibtidaiyah Al-Anwar Sarang using a quantitative approach, involving 37 purposively selected fifth-grade students. Data were collected through questionnaires, complemented by in-depth observations, and analyzed using linear regression and the Sobel test. The results indicated that CSM significantly enhances students' self-confidence (p<0.05) and that self-confidence, in turn, significantly improves students' public speaking skills (p<0.05). However, CSM did not directly affect public speaking skills (p>0.05); instead, self-confidence acted as a mediator. The Sobel test confirmed the significant mediating role of self-confidence, with a t-value of 4.637. The study concludes that while CSM indi